Who Benefits More from E-Learning? A Gender-Based SEM-PLS Analysis of Adoption, Outcomes, and Future Optimization Paths in Digital Education - Shannaq, Boumedyen; Almaqbali, Said; Leow, Meng-Chew; Marhoubi, Asmaa H.; Ong, Lee-Yeng (Journal of Posthumanism, 2025)
The current research analyzes how essential variables influence E-Learning Benefits (ELB) through gender-based perspectives for students enrolled at the university level. A research analysis using SEM and MGA examines the impact of MOT, DR, and PEU and PU on ELE and ELB across genders from students at the University. The results stemmed from 330 participants (174 females and 156 males) who completed structured surveys. Data shows that females show a stronger relationship between motivational factors leading to educational benefits compared to males, as evidenced by a 0.023 significance value. The variable DR demonstrates a positive relationship with ELB outcomes in both male (β = 0.521) and female students (β = 0.298). The results indicate that females experience greater ELE impacts from PEU (p = 0.037) than males experience greater ELE impacts from PU (p = 0.007). The research did not show any significant indirect effects between variables in either study group. The study suggests that institutions should work on motivating female students through specific strategies and utilize tools with clear benefits for male students, as they enhance digital readiness for all students.